Evaluation of Mortality Frequency in Cardiogenic Shock in Anterior Wall Myocardial Infarction in the Patients Presented to Lady Reading Hospital, Peshawar - Ijaz Ahmad, Jabar Ali, Imran Ellahi Soomroo, Sarfraz Ali Mangi, Vickee Kumar, Muhammad Aslam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The insufficient supply oxygen and blood to the myocardium is characterized by the coronary artery disease. The coronary arteries occlusion leads to this condition. The plaques formation in coronary arteries lumen is indicative of the condition. These plaques impede blood flow. It is a major concern worldwide. Objective: To evaluate the mortality frequency in cardiogenic shock in anterior wall myocardial infarction in patients presenting to Lady Reading Hospital, Peshawar. Study Design: It is a descriptive case study conducted at department of Cardiology, Lady Reading Hospital Peshawar and NICVD, Nawabshah. This study was conducted from 1st June 2021 to 30th November 2021. Subjects and Methods: A total of 139 patients diagnosed with cardiogenic shock were selected for the study. According to the operational definition the followed up of all patients till discharge and mortality was recorded. Results: The age range of the patients selected for the study was 18-70 years. The mean of age was 47.841±6.66 years, mean weight 83.259±7.39 Kg and mean duration of symptoms was 8.870±3.76 hours. Male patients were 77.7% and females were 22.3%. Mortality was seen in 20.9% patients. Conclusion: Patients with anterior wall myocardial infarction and cardiogenic shock undergoing percutaneous coronary intervention have better clinical out-comes. The decreased mortality is also observed. Without the delay of time the patients must be transferred to the primary percutaneous coronary intervention facility if it is far away. There is need to establish more primary percutaneous coronary intervention centers. Keywords: Anterior wall myocardial infarction, cardiogenic shock, mortality.